2009
DOI: 10.1002/jrs.2235
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of rotational CARS thermometry in fuel‐rich hydrocarbon flames by inclusion of N2‐H2 Raman line widths

Abstract: In rotational coherent anti-Stokes Raman spectroscopy (CARS) thermometry applied to air-fed flames, the temperature sensitivity mainly depends on the intensity distribution of the nitrogen spectral lines. Temperatures are estimated by numerical fitting of theoretical spectra to experimental ones, and one uncertainty in the calculation of theoretical CARS spectra for specific flame conditions is the accuracy in utilized line-broadening coefficients. In a previous article, self-broadened N 2 -N 2 line widths wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Further, it was observed that with the use of self-broadened N 2 -N 2 Raman line widths only, the evaluated CARS temperatures systematically underestimated the reference temperature by as much as 6-9% at the highest hydrogen concentration (90%). These results are in qualitative agreement with previous results, [13] where interchanging the Raman line widths from N 2 -N 2 with N 2 -H 2 raised the evaluated flame temperatures by about 2%, when probing nitrogen in the product gases of a rich hydrocarbon flame ( = 2.5) with a hydrogen concentration of about 20%.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Further, it was observed that with the use of self-broadened N 2 -N 2 Raman line widths only, the evaluated CARS temperatures systematically underestimated the reference temperature by as much as 6-9% at the highest hydrogen concentration (90%). These results are in qualitative agreement with previous results, [13] where interchanging the Raman line widths from N 2 -N 2 with N 2 -H 2 raised the evaluated flame temperatures by about 2%, when probing nitrogen in the product gases of a rich hydrocarbon flame ( = 2.5) with a hydrogen concentration of about 20%.…”
Section: Discussionsupporting
confidence: 82%
“…Bohlin et al included in evaluations of rotational CARS spectra from sooting premixed ethylene/air flames. [13] It was demonstrated that at an equivalence ratio of 2.5, at which the hydrogen concentration can be as high as 20%, the use of adequate N 2 -H 2 Raman line widths instead of assuming that N 2 -N 2 Raman line widths could be used also for this part, increased the temperature evaluation by 36 K.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] When including these Raman linewidths 7 in evaluations of N 2 RCARS spectra, recorded in the product gases of a rich hydrocarbon flame containing 20% H 2 , the predicted temperature was systematically increased by about 2%. 8 This behavior was confirmed in a subsequent study, probing N 2 in binary mixtures with H 2 at calibrated temperature conditions below 800 K. 9 Here, it was shown that when neglecting the effects on the N 2 spectral lines in the environment dominated by collisions with H 2 , predicted temperatures from N 2 RCARS could be underestimated by as much as 6%-7%. However, by modifying the Raman linewidth model to incorporate each of the speciesspecific contributions to the broadening coefficient, weighted in accordance with their relative mole fractions, the thermometry was improved.…”
Section: Introductionmentioning
confidence: 60%
“…Gao et al [126] presented a new line shape model for molecular H 2 that was developed and tested for ambient pressure applications. In a related paper, Bohlin et al [127] published an improvement of rotational CARS thermometry for fuel-rich hydrocarbon flames by inclusion of N 2 -H 2 Raman line widths. Peng et al [128] presented the details of a simple setup for hybrid coherent Raman microspectroscopy.…”
Section: Coherent Anti-stokes Raman Spectroscopymentioning
confidence: 99%